Effect of Aluminum Oxide on the Mechanical Properties of ceramic crucibles prepared by slip casting from local kaolin clay material. - Ammar Thamer Karim, (Zien Journals, 2022)
In this Article, the structural and mechanical properties were studied for the manufactured ceramics crucibles by the slip casting method from local clay materials after adding different percentages of aluminum oxide, where the adding percentages were ranged between (0.0 - 50 wt%). A number of parameters affecting the final properties of the local kaolinite sample were studied, such as the sintering temperature, which ranged between (1000-1500 ºC) and the adding percentages of the aluminum oxide. The apparent density and porosity analyze showed that increasing the adding percentages of the aluminum oxide led to an increase in the porosity at the high percentages, while low percentages lead to an increase in the density of the samples. On the other hand, the results showed that the increase of the aluminum oxide leads to the decrease of the samples hardness at the high sintering temperature, while the opposite occurs at the low sintering temperature.
Keywords: Ceramic crucibles; slip casting; sintering; alumina oxide